Açorianos e suas estratégias de inserção socioeconômica no povoamento do sul da América portuguesa (Rio Pardo, segunda metade do século XVIII) - Rosa, Cibele Caroline da (Universidade do Vale do Rio dos Sinos, 2020)
This research analyzes strategies of social and economical insertion of Azoreans immigrants in the south of the Portuguese America. The chosen place is the parish of Nossa Senhora do Rosário de Rio Pardo throughout the second half of the XVIII century. In this period, many residents from the nine islands that form the Azores archipelago (Insular Portugal) moved to populate America, with highlights to the border areas such as the then Continent of Rio Grande de São Pedro, a region of interest among the Portuguese and Spanish crown. The research tried to identify this migration process rethinking the motivations that led islanders to leave the archipelago, as well as the arrival in Rio Pardo. With focus given to the actions of such immigrants, multiple strategies have been shown from these subjects to the establishment in the region, notedly from border regions and constant moving places. From the serial analysis from paroquial sources (baptism registries and matrimonies from Nossa Senhora do Rosário de Rio Pardo), list of residents who own lands and animals in the continent and other sources, it is notable that the Azorean presence happened in the first years of the foundation that is verified through spiritual relationships and selecting a godparent, as well as access to the lands and ongoing economical activities at the time. Through conceptions of an old regime in the Tropics, liked to the meteorological inspirations of the Italian micro-history, it is demonstrated that not all those that migrated from the islands to the region of Rio Pardo formed a poor and submissive mass of people from the Portuguese crown. With nominative crossing, it was possible to analyze strategies of a group of immigrants that fed a network of multiple relations imbricated socially and economically.
Keywords: Migração Açoriana; Continente de Rio Grande de São Pedro; Antigo Regime nos Trópicos; Estratégias de Inserção Sociais e Econômicas; Rio Pardo; Azorean Migration; Continent of Rio Grande de São Pedro; Old Regime in the Tropics; Strategies of Social and Economical insertion; Rio Pardo; ACCNPQ::Ciências Humanas::História